(untitled) (Zien Journal of Social Sciences and Humanities, 2021)
The article investigates the place and role of psycho physiological and psycholinguistic means on creating national character on the example of the story by Nabi Jaloliddin “Chuvalchang yoqqan kecha”. The author’s proficiency of creating the image, the place of a detail in revealing character’s mentality, enriching of an epic feeling with national customs and traditions are analyzed through examples.